Case‐based learning (CBL) in undergraduate health professions education: A realist review. - Daly, Ronan; Tunney, Elizabeth; Spooner, Muirne; Offiah, Gozie; Flood, Karen; Kent, Fiona (Medical Education, 2026)
Introduction: Case‐based learning (CBL) has been adopted internationally, although there is significant heterogeneity in implementation and delivery. It is unclear how this pedagogical approach is experienced across contexts, among different groups of students, and the important aspects of implementation. The aim of this study was to understand the mechanisms that enable CBL to facilitate learning in undergraduate health professions education, for whom and in what contexts. Methods: A realist review was adopted to explore the literature on CBL. Initial programme theories were derived from the CBL literature and based on adult learning theory and inquiry‐based learning. 5731 abstracts investigating CBL in undergraduate HPE courses were screened in duplicate. 436 full‐text papers were screened and assessed for rigour and relevance, resulting in 25 papers suitable for inclusion in the final analysis. Results: Seven programme theories were developed from our review. Institutional, implementation and student‐level factors were found to impact outcomes such as exam performance, participation and clinical reasoning. A lack of institutional support and recognition of faculty contribution to CBL results in poorer learning outcomes. Clinical facilitators promote student engagement, and authentic multimodal cases afford students the opportunity to step into their future roles. When assessment focuses solely on behaviours and teamwork is not fostered, negative group dynamics may result. Discussion: Our realist review provides insight for healthcare educators on how best to implement CBL to optimise academic, skill and behavioural outcomes for undergraduate students. Fostering student trust in learning through access to clinician facilitators and authentic cases leads to improved learning outcomes. Recognition of faculty and student efforts to contribute to CBL is essential for successful implementation. The facilitation of a safe and secure group learning environment is required for students to meaningfully engage with CBL. Case‐based Learning in #HPE: a realist review explores what works in #CBL, for whom, and under what circumstances, providing key insights for healthcare educators. #MedEd